ETHICS AND RELIGION IN THE STREAM OF LIFE - Nandhikkara, Jose (Journal of Dharma, 2013)
Ethics, Creed and Cult are constitutive of all religions; there is no religion without rules for moral behaviour. More importantly human beings are fundamentally ethical beings so much so that they are called homo ethicus. Homo ethicus is also intimately related to homo religiosus in the stream of life. Traditionally religions were the custodians of Ethics and moral instructions were included in the scriptures and handed down through tradition. Life and words of the founders of religious paths are normative for believers for deciding what is good, right and just. The cultic celebrations are also occasions for ethical instructions. For many believers it is religion that directs their ethical decisions and they would assert that religion is necessary and sufficient to live ethically. The religions also generally take into account how the traditional ethical teaching can be interpreted and updated for solving complex moral problems in the modern world. Such contemporary interpretations argue that Scriptures and Sacred Traditions do not exhaust full range of ethics, though contemporary ethical decisions cannot be against the normative traditions. The advancements in science and technology, changed social scenarios in economics, commerce, politics, etc. demand new ethical solutions. Many religions like Christianity have eschatological goals also for ethical behaviour whereas religions like Confucianism aim at maintenance and propriety of relationships.